Adaptive decentralized fuzzy dynamic surface control scheme for a class of nonlinear large-scale systems with input and interconnection delays. (July 2020) - Baigzadehnoe, Barmak; Rahmani, Zahra; Khosravi, Alireza; Rezaie, Behrooz
Abstract: This paper is focused on the decentralized tracking control problem of nonlinear large-scale systems with immeasurable states and unknown nonlinearities in each subsystems and their interconnections in the presence of unknown interconnection delays and uncertain input delays. To deal with inaccessible states and unknown nonlinearities, a fuzzy state observer is firstly constructed. Then, appropriate changes of coordinates are defined to cope with the problem of uncertain input delays and design dynamic surface control strategy for unknown nonlinear interconnected systems. In the design procedures, appropriate Lyapunov–Krasovskii functions are introduced to conquer the difficulties arising from interconnection delays with unknown upper bounds. it is also proven that the proposed method can ensure that all signals of the closed loop large-scale systems in the presence of both interconnection and input delays which have not been considered in previous literature are uniformly ultimately bounded. Furthermore, by appropriate selection of design parameters and matrices, the observation errors as well as the tracking errors converge to small desired values. Finally, to illustrate the effectiveness and efficiency of the proposed decentralized control scheme, numerical simulations are performed.